Mechanism and therapeutic potential of liver injury induced by cholesterol-associated proteins - Zhou, Yourong; Cao, Yashi; Yin, Yiming; Xu, Zhifei; Yang, Xiaochun; Yang, Bo; Luo, Peihua; Yan, Hao; He, Qiaojun (Frontiers in Pharmacology, 2025)
Cholesterol, the most abundant sterol molecule in mammalian organisms, serves not only as a fundamental structural component of cell membranes but also as a critical regulator of cellular signaling and function. Cholesterol-associated proteins can mediate liver injury either directly by influencing cholesterol levels or through non-cholesterol pathways. These non-cholesterol pathways, which operate independently of cholesterol’s traditional metabolic functions, are regulated by specific transcription factors, proteins and receptors. Dysregulation of cholesterol-associated can disrupt cellular homeostasis, leading to liver injury, metabolic disorders, and even tumorigenesis. In this article, we explore the mechanisms by which cholesterol-associated proteins contribute to liver injury via both classical cholesterol pathways and non-cholesterol pathways, and discuss their potential as therapeutic targets for liver-related diseases.